2012
DOI: 10.1530/rep-12-0048
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of testosterone and 17β-estradiol on gonadal development in five anuran species

Abstract: Sex hormones are essential for sexual differentiation and play a key role in the development of gonads in amphibians. The goal of this study was to evaluate the influence of exogenous sex steroids, testosterone, and 17b-estradiol (E 2 ) on development of gonads in five anuran species differing in their evolutionary positions, sex determination, and mode of gonadogenesis. We found that in two closely related species of fire-bellied toad, Bombina bombina and Bombina variegata, testosterone and E 2 exposure resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 26 publications
(41 reference statements)
1
29
0
Order By: Relevance
“…1). Thus, in both anuran and urodele amphibians, the ovary is an ovisac [Dumond et al, 2008a;Piprek et al, 2012]. In S. tropicalis , ovary differentiation seems to occur along an antero-posterior gradient [El Jamil et al, 2008].…”
Section: Gonad Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Thus, in both anuran and urodele amphibians, the ovary is an ovisac [Dumond et al, 2008a;Piprek et al, 2012]. In S. tropicalis , ovary differentiation seems to occur along an antero-posterior gradient [El Jamil et al, 2008].…”
Section: Gonad Differentiationmentioning
confidence: 99%
“…This has been suspected from numerous experiments in which sex reversal occurred following addition of exogenous steroids to the rearing water or injection to tadpoles [for review, see Nakamura, 2010;Flament et al, 2011]. The sensitivity of several anuran species to testosterone and 17β-estradiol was studied recently [Piprek et al, 2012]. It was also shown that testosterone propionate and estradiol could alter sex ratios in the Indian skipper frog Euphlyctis cyanophlyctis [Phuge and Gramapurohit, 2015].…”
Section: Importance Of Steroidsmentioning
confidence: 99%
“…Not only fish but also amphibians and reptiles are sensitive to testosterone in the aquatic environment. Piprek et al (2012) carried out research on two species of frogs Bombina bombina and Bombina variegata, during which they showed that this hormone causes differentiation of gonads and promotes the creation of intersex individuals. The assessment of the impact of pollution on aquatic ecosystems is an extremely difficult task due to the different sensitivity of aquatic organisms to chemical compounds present in the environment, and due to bioaccumulation in the upper links of the trophic chain, it is difficult to determine the longterm effects of their presence in water (Torres et al 2008;Ahmed et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gonadal differentiation is highly influenced by steroid hormones in amphibian . Endogenous androgens and estrogens have been assumed to act as the natural inducers of testicular and ovarian differentiation, respectively . StAR , CYP17 and CYP19 are indispensable for sex‐steroid production in the vertebrate gonads .…”
Section: Introductionmentioning
confidence: 99%